Menumbuhkan Literasi Numerasi Melalui Model PBL Berbantu Media Papan Berpaku - Wahyuni, Siska Dwi; Wakhyudin, Husni; Suchaeroh; Nursyahidah, Farida (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study was to describe the implementation of the Problem-Based Learning (PBL) learning model through the use of nailed boards to encourage increased numeracy literacy in students. The study is included in quantitative research using pre-experimental methods through purposive random sampling techniques. In the one-group pretest-posttest design, the research subjects consisted of class III B students at SDN Siwalan. The results of the study proved that the effectiveness of the application of the PBL Model through the use of nailed boards was found to foster student numeracy literacy in the class. The form of the instrument used as a tool for measuring learning outcomes was the student's pretest and posttest scores. The average pretest score was 42.2, while after the application of the PBL model with nailed boards, the average posttest score increased to 81.0. This difference is significant with a pretest-posttest value of <0.05. Thus, the PBL model assisted by nailed boards has been proven to encourage increased numeracy literacy in class III B students at SDN Siwalan.